1977
DOI: 10.1128/jb.131.3.1023-1025.1977
|View full text |Cite
|
Sign up to set email alerts
|

Propionate-induced synthesis of odd-chain-length fatty acids by Escherichia coli

Abstract: Exogenous propionate is incorporated in vivo by Escherichia coli as a primer to produce lipids with fatty acids of odd chain lengths. This provides a method for the specific labeling of the three terminal carbons in the fatty acyl chains of phospholipids. ' Data from reference 2. c Deuterochloroform solvent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 8 publications
1
30
0
Order By: Relevance
“…However, some studies have shown that it is more likely the other way around in bacteria. Microbial OCFAs are mainly formed through elongation of Pr [32,33]. With the present mouse experiments we support the latter.…”
Section: Discussionsupporting
confidence: 83%
“…However, some studies have shown that it is more likely the other way around in bacteria. Microbial OCFAs are mainly formed through elongation of Pr [32,33]. With the present mouse experiments we support the latter.…”
Section: Discussionsupporting
confidence: 83%
“…In other words, propionyl‐CoA became the more preferred substrate than acetyl‐CoA in the initialization step of fatty acid synthesis of the strain which cooverexpressed BsfabH 1 and prpE . However, even straight chain FFAs were the main component of cell membrane (Ingram et al, ), which is highly related on cell growth, rather than odd chain straight FFAs. This manipulation of cooverexpressed BsfabH 1 and prpE may disrupt the balance of distribution of acetyl‐CoA among cell growth, acetate formation and free fatty acid production pathways, and led to higher acetate accumulation and lower free fatty acid production.…”
Section: Resultsmentioning
confidence: 99%
“…The chain numbers of most straight FFAs produced by microorganisms or plants are even, a small amount of odd straight‐chain FFAs are produced in some stomach and ruminant bacteria (Kim et al, ; Or‐Rashid et al, ). In previous study, propionate can induce synthesis of very small amount of odd‐chain‐length fatty acids by wild type Escherichia coli K‐12 (Ingram et al, ). Tseng and Prather () engineered and optimized three modular metabolic pathways, which was validated separately and then assembled together, for the synthesis of odd short chain molecules such as propionate, trans‐2‐pentenoate, valerate, and pentanol.…”
Section: Introductionmentioning
confidence: 91%
“…One of the surprising observations made here was the identification of an AHL (C 7 -HSL) with an odd number of carbons in the acyl chain. Such an AHL has not been described previously, although fatty acids and polyketides with odd numbers of carbons in the chain have been described (O'Hagan, 1991;Ingram et al, 1977). These arise via a pathway that uses propionyl-CoA and malonyl-CoA as the respective chain starter and extender units.…”
Section: Discussionmentioning
confidence: 98%